Nutritional Models of Experimentally-Induced Subacute Ruminal Acidosis (SARA) Differ in Their Impact on Rumen and Hindgut Bacterial Communities in Dairy Cows - Plaizier, Jan C.; Li, Shucong; Tun, Hein M.; Khafipour, Ehsan (Frontiers in Microbiology, 2017)
Effects of subacute ruminal acidosis (SARA) challenges on the bacteria in rumen fluid, cecal digesta, and feces of dairy cows were determined using 454 pyrosequencing and real-time quantitative PCR. Six non-lactating Holstein cows with cannulas in the rumen and cecum were used in a 3 × 3 Latin square arrangement of treatments. During the first 3 wk of each experimental period, cows received a control diet containing 70% forages on a dry matter (DM) basis. In wk 4 of each period, cows received one of three diets: 1) the control diet; 2) a diet in which 34% of the dietary DM was replaced with pellets of ground wheat and barley (GBSC); or 3) a diet in which 37% of dietary DM was replaced with pellets of ground alfalfa (APSC). Rumen fluid, cecal digesta and feces were collected on d 5 of wk 4 of each period and the composition of the bacterial community was studied. Rumen fermentation responses were reported in a companion study. Both SARA-inducing challenges resulted in similar digesta pH depressions (as shown by the companion study), and reduced bacterial richness and diversity in rumen fluid, but GBSC had the larger effect. None of the challenges affected these measures in cecal digesta, and only GBSC reduced bacterial richness and diversity in feces. Only GBSC reduced the abundance of Bacteroidetes in rumen fluid. Associations among the abundances of the gram-negative bacterial phyla and the concentrations of free lipopolysaccharide endotoxin reported in the companion study in the rumen could not be established. Effects of the GBSC on the abundances of bacterial genera identified by pyrosequencing in the rumen, cecum and feces were limited. The APSC did not affect any of these abundances. Both challenges increased the abundances of several starch, pectin, xylan, dextrin, lactate, succinate, and sugar fermenting bacterial species in the rumen, cecum, and feces as determined by qPCR. Only GBSC increased that of Megasphaera elsdenii in the rumen. Both challenges decreased the abundance of Streptococcus bovis, and increased that of Escherichia coli, in cecal digesta and feces, with GBSC having the larger effect. These results showed that the